2015
DOI: 10.1167/15.3.16
|View full text |Cite
|
Sign up to set email alerts
|

Optical angular constancy is maintained as a navigational control strategy when pursuing robots moving along complex pathways

Abstract: The optical navigational control strategy used to intercept moving targets was explored using a real-world object that travels along complex, evasive pathways. Fielders ran across a gymnasium attempting to catch a moving robot that varied in speed and direction, while ongoing position was measured using an infrared motion-capture system. Fielder running paths were compared with the predictions of three lateral control models, each based on maintaining a particular optical angle relative to the robotic target: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Decisions regarding direction changes are important in chase-and-escape interactions. Previous studies on many animals, ranging from dragonflies 68 , to fish 9 and dogs 10 , to humans 1113 , have shown that a strategy called constant bearing is commonly employed to intercept a moving target, such as prey, a frisbee, or a flying ball. When the speed of the pursuer is equal to or faster than that of the evader, this interception strategy is theoretically unbeatable without a sensorimotor delay 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Decisions regarding direction changes are important in chase-and-escape interactions. Previous studies on many animals, ranging from dragonflies 68 , to fish 9 and dogs 10 , to humans 1113 , have shown that a strategy called constant bearing is commonly employed to intercept a moving target, such as prey, a frisbee, or a flying ball. When the speed of the pursuer is equal to or faster than that of the evader, this interception strategy is theoretically unbeatable without a sensorimotor delay 14 .…”
Section: Introductionmentioning
confidence: 99%